DATA ENVELOPMENT ANALYSIS (DEA) EFFICIENCY OF ISLAMIC BANKS IN ASEAN: A CROSS-COUNTRY COMPARATIVE EXAMINATION OF INTERMEDIATION AND PRODUCTION EFFICIENCY APROACH - Faturohman, Taufik .; Maharani, Auryn Khansa; Sudrajad, Oktofa Yudha; Irawan, Atika (FEB Universitas Sam Ratulangi Manado, 2019)
Abstract: In 2015 ASEAN leaders agreed to form an integrated market called ASEANEconomic Community (AEC) that enables countries in Southeast Asia to trade goodsand services more easily, attracting strong demand from investors and heightened thecompetition in the industry. The heightened of competition should encourage banks toreduce operating costs and, hence, eliminate inefficiencies in the banking industry. Theobjective of this study is to examine the relative efficiency scores of Islamic banksacross six countries in ASEAN from 2011 to 2018. The study implement DataEnvelopment Analysis under the intermediation and production approach. Despite therapid growth of the Islamic banking, examination of Islamic banks at a cross-countrylevel is still at its infancy, especially in ASEAN. Therefore, this research aims to fill thegap in the literature by providing the empirical evidence on the efficiency of Islamicbanks in ASEAN during 2011-2018. The analysis is divided into two frontiers, namelysingle-multiyear frontier to examine the efficiency trends of all ASEAN countries ineight years and cross-sectional frontier to compare the efficiency of countries inASEAN per year. The single multi-year frontier shows that the Philippines, Malaysia,Thailand and Singapore presents positive trend efficiency, while Indonesia fell, andBrunei fluctuated. Cross-sectional frontier shows that Brunei is the country that is mostfrequent in achieving optimum efficiency. Furthermore, the higher the efficiency of anIslamic bankingKeywords: Data Envelopment, Analysis (DEA), Efficiency, Islamic Banks, Association of Southeast Asian Nations (ASEAN)